NEW MODELS OF SOCIAL AND ECONOMIC EVOLUTION IN SPAIN - Yu. V. Slivchikova; E. V. Kryukova (Сравнительная политика)
The economic crisis in Spain that began in 2008 led to the deep social discontent that later turned into the movement of «Indignant», citizens tiered of economic restrictions, unemployment, corruption scandals. That movement brought new political parties to the traditional bipolar Spanish political system, destroying it and showing to the establishment that the country needs urgent measures to be taken. The non-confi dence motion showed the inability of the mainstream parties to solve the existing problems that collapse the country. That helped a lot to the appearance of a new populist party called Podemos that offered immediately simple solutions to the national economic challenges. Unfortunately and logically becoming the third party in Spain didn’t help to Podemos to solve all the current problems and it was obliged to give way to another young party – Ciudadanos. The party that originally was created to defend the rights of Spanish people in Catalonia soon realized the need to reach the national scale to be heard and for this purpose created a program of social and economic reforms for the whole country. The study sets out to analyze the reasons of the success of new Spanish parties as well as to compare their programs and watch the new vector of political evolution in Spain.